Anti-Competitive Behaviors through Consumer Switching Constraints Imposed by Mobile Telecommunications Firms in the Philippines - Chua, Gian Angelo E. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
This note, adding to the development of legal and economic authors on switching costs, postulates that the collectively dominant incumbent mobile telecommunication service providers--Globe and Smart--in imposing lock-in periods and mobile number (un)portability are abusing their dominant position. The substantial and strategic creation or increase by a dominant firm of switching costs, which are the monetary and non-monetary costs consumers incur in switching from one provider to another, constitutes abuse under Section 15 of the Philippine Competition Act.
Keywords: Telecommunication - Business enterprises - Philippines; Telecommunication - Business enterprises - Philippines - Violations; Competition - Law